Fingerprinting Method for Phylogenetic Classification and Identification of Microorganisms Based on Variation in 16S rRNA Gene Sequences. (July 2000) - Raghava, Gajendra P.S.; Solanki, Rajesh J.; Soni, Vishal; Agrawal, Pushpa
The paper describes a method for the classification and identification of microorganisms based on variations in 16S rRNA sequences. The 16S rRNA is one of the most conserved molecules within a cell. The nature of the variable and spacer regions has been found to be specific to a given organism. Thus, the method presented here can be very useful for the classification and identification of microorganisms for which very little information is available. To automate the method, a comprehensive computer program called FPMAP has been developed for the analysis of restriction fragment pattern data. The method involves the restriction digestion of genomic DNA, preferably using four-cutters that may recognize 6–9 sites within the 16S rDNA. The fragments are separated on a polyacrylamide gel along with a suitable marker, then transferred into a nylon membrane and hybridized with a radiolabeled 16S rDNA probe. After autoradiography, the fragment sizes are calculated, and the data are analyzed using the FPMAP software. We demonstrate that the method can be used for identification of strains of Streptomyces and mycobacteria . The software is available from our ftp site ftp://imtech.chd.nic.in/pub/com/fpmap/unix/.